Proceedings of the 2011 Winter Simulation Conference (WSC) 2011
DOI: 10.1109/wsc.2011.6148066
|View full text |Cite
|
Sign up to set email alerts
|

SIMARAIL: Simulation based optimization software for scheduling railway network

Abstract: This paper presents an event-driven simulation-based optimization method for solving the train timetabling problem to minimize the total traveling time in the hybrid single and double track railway networks. The simulation approach is well applied for solving the train timetabling problems. In present simulation model, the stations and block sections of the railway network are respectively considered as the nodes and edges of the network model. The developed software named SIMARAIL has the capability of schedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The purpose of this section is to show which problems have previously been studied in Discrete event simulation is a commonly used tool in railroad logistics. One of the most common uses is train scheduling Sajedinejad et al 2011). …”
Section: Locomotive Research Applicationsmentioning
confidence: 99%
“…The purpose of this section is to show which problems have previously been studied in Discrete event simulation is a commonly used tool in railroad logistics. One of the most common uses is train scheduling Sajedinejad et al 2011). …”
Section: Locomotive Research Applicationsmentioning
confidence: 99%
“…As train timetabling problem is known to be NP-hard [5,7,15,33], a meta-heuristic algorithms have been applied to solve it. It has been shown that GA has high potential in finding the global optimum in a large, poorly defined search space even in the presence of difficulties such as high dimensionality, multi-modality, discontinuity, and noise [15].…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…It has been shown that GA has high potential in finding the global optimum in a large, poorly defined search space even in the presence of difficulties such as high dimensionality, multi-modality, discontinuity, and noise [15]. GA has been successfully applied to combinatorial problems and is able to handle huge search spaces as those arising in scheduling problems [33].…”
Section: Genetic Algorithmmentioning
confidence: 99%
See 2 more Smart Citations